2016
DOI: 10.3390/atmos7090118
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Heavy Rain over the Southeastern Tibetan Plateau

Abstract: This research systematically studied heavy rain that occurred on 5 August 2014 over the southeastern Tibetan Plateau (31 • N-35 • N, 96 • E-103 • E) using orbital data from the Tropical Rainfall Measuring Mission (TRMM) precipitation radar (PR), the TRMM Multi-satellite Precipitation Analysis (TMPA) products, and the European Centre for Medium-range Weather Forecast (ECMWF) Re-Analysis Interim reanalysis data (ERA-Interim). The data studied included spatial and temporal distributions of the precipitation; hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…However, some investigations on extreme precipitation only involved partial areas of the QTP [26][27][28][29], and precipitation extremes for the entire QTP separated from China have not been previously investigated in detail. Moreover, many studies have confirmed the impact of complex topography over the QTP on spatiotemporal variations of precipitation [30][31][32]; nevertheless, whether and what kind of topographical influence exists in relation to changes of extreme precipitation still needs further study. Zhang et al reported there was a negative correlation between precipitation extremes and elevation in the Hengduan Mountains region [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, some investigations on extreme precipitation only involved partial areas of the QTP [26][27][28][29], and precipitation extremes for the entire QTP separated from China have not been previously investigated in detail. Moreover, many studies have confirmed the impact of complex topography over the QTP on spatiotemporal variations of precipitation [30][31][32]; nevertheless, whether and what kind of topographical influence exists in relation to changes of extreme precipitation still needs further study. Zhang et al reported there was a negative correlation between precipitation extremes and elevation in the Hengduan Mountains region [29].…”
Section: Introductionmentioning
confidence: 99%
“…After sunset, the air temperature drops abruptly, the convective activity rapidly weakens and precipitation sharply decreases. The vertical differences are likely to be derived from the diversity of the precipitation mechanism in mountainous areas, which makes the influence of convective precipitation in different altitude zones inconsistent [39]. At high elevations, the mountain peaks rising one after another can block water vapor, and the hydrothermal conditions including the diurnal temperature range, actual evapotranspiration, etc.…”
Section: Diurnal Variationmentioning
confidence: 99%
“…On spatial scales, precipitation patterns are influenced by the orography [6][7][8][9][10] and land cover [11,12]. On temporal scales, precipitation patterns are driven by different temporal cycles of the large-scale atmospheric circulation [13] and diurnal warming [14].…”
Section: Introductionmentioning
confidence: 99%